Global and local correlations of Hajnal's historical household formation markers: A geographically weighted approach - Mikołaj Szołtysek; Bartosz Ogoŕek (Hungarian Demographic Research Institute, 2020)
Previous scholarship has hypothesised a global correlation between marriage age, premarital service in husbandry, the extent to which marriage coincided with the assumption of household headship, and the nuclear household structure. According to John Hajnal, these were the axial principles of historical household formation systems. However, whether such correlations apply universally across Europe remains uncertain. We test this possibility by applying both global and local (geographically weighted) measures of correlation to data for 256 rural populations from historic Europe. We demonstrate that the local correlations diverge considerably from the global results. The mutual associations between household formation markers exhibit considerable spatial drifts or important spatial gradients, and the numbers of the joint combinations of these associations far exceed those predicted by Hajnal. We conclude by arguing that the global relationship patterns that Hajnal promoted may lead to incorrect interpretations of historical family systems, and may detract from our understanding of their actual mechanics.
Keywords: 300; spatial nonstationarity; household formation; family systems; census microdata; historical demography; spatial analysis; geographically weighted correlation